Improving EFL Students' TOEFL Listening Scores Through Signpost Words and Guided Note-Taking: A Pre-Test and Post-Test Experimental Study - Zetira Ahmad (Indonesian Journal of Multidisciplinary Scientific Studies, 2026)
The listening comprehension section of the Test of English as a Foreign Language (TOEFL) represents a formidable academic hurdle for English as a Foreign Language (EFL) learners, primarily due to the rapid, real-time processing of high-density academic vocabulary, natural speech rates, and highly complex, non-linear lecture structures. This study systematically investigates the pedagogical effectiveness of teaching explicit structural lecture cues—specifically "signpost words" or rhetorical transition markers—combined with systematic, guided note-taking strategies to improve TOEFL listening proficiency and mitigate academic listening anxiety. Using a quantitative, one-group pre-test and post-test experimental research design, a cohort of 40 university students from non-English majors underwent an intensive, 6-week instructional intervention focused on cognitive load reduction and strategic auditory processing. The research utilized parallel versions of the official TOEFL ITP listening section as diagnostic instruments to measure empirical gains, alongside qualitative student self-reports to monitor affective shifts. The empirical results demonstrated a highly significant, statistical increase in students' listening performance, with the group's mean score rising from a baseline of 432 to 512 on the TOEFL ITP scale ( , ). A detailed sub-score analysis revealed that the most substantial gains occurred in main-idea and detail-oriented question items, which directly correlated with the students’ newly acquired ability to filter raw speech and map lectures structurally. Ultimately, this paper details how explicit, strategy-based instruction in recognizing rhetorical markers effectively reduces cognitive fatigue, optimizes working memory limits, and fosters active, highly strategic academic listening habits that are vital for future success in English-Medium Instruction (EMI) university classrooms.